Damascus Image before and after the Fire: A Study in Maqamat Sip of Nectar in the Description of Fire - Alzboon, Ragda; Ammayrah, Hanan (Dirasat: Human and Social Sciences, 2021)
The present study explores the image of fire of Damascus in Maqamat Sip of Nectar in the Description of Fire by Salahu-Din Khalil bin Aybak Al-Safadi. It also examines the details of this important event to which Damascus was exposed in the middle of the eighth century AH. The study is based on revealing the substantive and stylistic dimensions of the image in this Maqamah, starting with describing the image of Damascus before and after the fire, and the psychological effects of this event on its people. The study discusses in detail the effect of addressing and its implications of the Maqamah structure. The study shows the themes of the image and its functions, and techniques of the descriptive sentence-structure in the literary picture of colorful and sensual data, and its impact on the aesthetics of the text and its significance in Maqamah.